Singing as a means of speech correction in preparing prospective special-education teachers in the people’s republic of China - Chai, Lihua (Professional Art Education, 2025)
The article examines the theoretical foundations and practice-oriented approaches to using singing as a tool for speech correction in the training of bachelor’s-level special education teachers in the People’s Republic of China (PRC).Methods and methodology. The methodology combines a comparative analysis of PRC curricula and standards, a structural-functional analysis of readiness components, a content analysis of dissertations and scholarly sources, and the modeling of assessment criteria and indicators. The study applies the following principles: interdisciplinarity (speech-language pathology—music pedagogy—psychology), practice-oriented learning (learning by doing), cultural sensitivity, and digital verification/monitoring of changes in speech parameters.Scientific novelty. The novelty lies in highlighting the readiness of future PRC special-education teachers to use singing for the speech correction of children with special educational needs—readiness that comprises motivational, cognitive, operational-activity, and reflective components—and in defining the system of pedagogical conditions for implementing the proposed training structure.Results. The structure of readiness is articulated as follows: (a) motivational orientation toward using singing; (b) cognitive awareness of the principles of speech-language pathology, vocal pedagogy, and the psychophysiology of speech; (c) operational-activity capacity to design vocal-corrective sessions, select repertoire, and individualize interventions; (d) reflective ability for self-assessment and adjustment of actions. The study substantiates the need for interdisciplinary integration (speech-language pathology—music therapy—vocal pedagogy), practice-oriented learning in partnership with schools and speech-language clinics, the use of culturally sensitive repertoire, and digital tools for monitoring speech dynamics. It describes integrated modules – «Music and Speech», «Vocal Rehabilitation for Children», practical singing sessions in a speech-therapy context, and training in emotional-communicative interaction—and identifies methods such as vocal-breathing exercises, eurhythmics, improvisational singing, intonation–movement techniques, articulatory-phonetic games, and multimedia interactive technologies. Conclusions. It is demonstrated that singing is an effective tool for the speech correction of children with special educational needs; the structure of readiness for professional activity among future special-education specialists is summarized. The practical significance lies in the potential to standardize university modules and implement inter-university practice and internship formats. Prospects for further research include expanding the evidence base for specific vocal protocols, improving digital monitoring tools, and adapting instructional materials across cultures.
Keywords: singing; speech correction; special education; PRC; music therapy; eurhythmics; bachelor level; readiness; competencies; arts integration